Causal association between helicobacter pylori and atherosclerosis: a two-sample Mendelian randomization - Xueyi Zhang; Yue Shi; Tielin Li; Ke Chang; Yongyan Gan; Yue Feng; Xianhua Zhou (BMC Cardiovascular Disorders, 2024)
Abstract Background Helicobacter pylori (H. pylori), according to a number of recent observational studies, is connected to atherosclerosis (AS). However, the link between H. pylori and AS is debatable. Methods In order to calculate the causal relationship between H. pylori and AS, we employed a two-sample Mendelian randomization (MR) analysis. The data for H. pylori were obtained from the IEU GWAS database ( https://gwas.mrcieu.ac.uk/datasets/ ) and the data for AS were obtained from the Finngen GWAS database ( https://r5.finngen.fi/ ). We selected single nucleotide polymorphisms with a threshold of 5 × 10–6 from earlier genome-wide association studies. MR was performed mainly using the inverse variance weighted (IVW) method. To ensure the reliability of the findings, We performed a leave-one-out sensitivity analysis to test for sensitivity. F-value was used to test weak instrument. Results A positive causal relationship between H. pylori OMP antibody levels and peripheral atherosclerosis was shown by our two-sample MR analysis (odds ratio (OR) = 1.33, 95% confidence interval (CI) = 1.14–1.54, P = 0.26E-03) using IVW. Additionally, there was a causative link between coronary atherosclerosis and H. pylori VacA antibody levels (IVW OR = 1.06, 95% CI = 1.01–1.10, P = 0.016). All the F-values were above 10. Conclusions This MR study discovered a causal link between H. pylori and AS. Different antibodies have different effects, so future researches are needed to figure out the exact mechanisms behind this link.